Development of Real-Time PCR Based on A137R Gene for the Detection of African Swine Fever Virus - Yin, Dan; Geng, Renhao; Lv, Hui; Bao, Chunhui; Shao, Hongxia; Ye, Jianqiang; Qian, Kun; Qin, Aijian (Frontiers in Veterinary Science, 2021)
African swine fever virus (ASFV) can infect domestic pigs and wild boars and causes huge economic losses in global swine industry. Therefore, early diagnosis of ASFV is very important for the control and eradication of African swine fever (ASF). In this study, a SYBR Green-based real-time polymerase chain reaction (PCR) assay targeting the viral encoded A137R gene was established for the detection of ASFV infection. For the evaluation of the established real-time PCR, 34 clinical samples were assessed by both the A137R gene-based real-time PCR and OIE-recommended TaqMan PCR. The results showed that 85.29% (29/34) were detected by A137R gene-based real-time PCR, but only 79.41% (27/34) positive using OIE-recommended TaqMan PCR. Moreover, no cross-reaction with other common swine pathogens was found in the A137R gene-based real-time PCR. These results demonstrated that the established real-time PCR assay in this study showed better performance than the OIE-recommended method in detecting ASFV from clinical samples, which could be applied for control and eradication programs of ASF.